2009
DOI: 10.1080/10715760902887276
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel modulators mediated alterations in NO-induced free radical generation and neutrophil membrane potential

Abstract: The present study investigated the effect of various ion (H+ and K+) channel modulators on nitric oxide (NO) donors (SNP and SNAP) induced free radical generation and on neutrophil membrane potential. Free radical generation was assessed by DCDHF-DA, using flow cytometry, while membrane potential was measured by a fluorescent dye, DiO-C5-(3). Neutrophil suspension in high potassium containing medium or following addition of NO donors (SNP, SNAP) to the neutrophil suspension led to free radical generation and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…1A and 1B). We found that at same concentrations, SNP was less effective than SNAP, in tune with reported slow release of NO by SNP (22). Generation of ROS was also confirmed by using an antioxidant, NAC (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…1A and 1B). We found that at same concentrations, SNP was less effective than SNAP, in tune with reported slow release of NO by SNP (22). Generation of ROS was also confirmed by using an antioxidant, NAC (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we have used commonly utilized NO donors, SNP and SNAP to explore reactive species modulation (14,15,17,19,21,22). Addition of NO donor, SNP or SNAP to the neutrophil suspension augmented ROS generation in a concentration-and time-dependent manner, as measured by DCF (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, NO was later identified to modulate diverse signaling cascades in neutrophil to regulate various functions such as adhesion, chemotaxis, phagocytosis, respiratory burst, apoptosis, and PMN-mediated bacterial killing or tissue damage (18). Previous studies from this laboratory have also demonstrated NO-mediated modulation of neutrophil free radical generation (19)(20)(21)(22).…”
mentioning
confidence: 99%